2022
DOI: 10.1161/hypertensionaha.122.19185
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Hypertension and Incident Infective Endocarditis

Abstract: Background: This study aimed to evaluate the association of hypertension with incident infective endocarditis (IE) by investigating the incidence of IE according to blood pressure levels using the National Health Insurance Service database. Methods: The data of 4 080 331 individuals linked to the health screening database in 2009 were retrieved (males, 55.08%; mean age, 47.12±14.13 years). From 2009 to 2018, the risk factors for the first episode of IE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(43 reference statements)
1
0
0
Order By: Relevance
“…In a recent publication using national cohort data, Lee et al demonstrated that increased blood pressure was associated with an increased risk for IE in dose-dependent manner. (12) In line with it, our study showed that HTN was an independent predictor of incident IE in the diabetic cohort as well. However, unlike DM which is known to cause immune dysfunction, angiopathy, or gastrointestinal and urinary dysmotility, the mechanism by which HTN causes incident IE is still unclear.…”
Section: Discussionsupporting
confidence: 80%
“…In a recent publication using national cohort data, Lee et al demonstrated that increased blood pressure was associated with an increased risk for IE in dose-dependent manner. (12) In line with it, our study showed that HTN was an independent predictor of incident IE in the diabetic cohort as well. However, unlike DM which is known to cause immune dysfunction, angiopathy, or gastrointestinal and urinary dysmotility, the mechanism by which HTN causes incident IE is still unclear.…”
Section: Discussionsupporting
confidence: 80%